Overexpression of family with sequence similarity 134, member B (FAM134B) in colon cancers and its tumor suppressive properties in vitro. Issue 10 (2nd October 2020) - Lee, Katherine Ting-Wei; Islam, Farhadul; Vider, Jelena; Martin, Jeremy; Chruścik, Anna; Lu, Cu-Tai; Gopalan, Vinod; Lam, Alfred King-yin
ABSTRACT: This study aims to investigate the overexpression-induced properties of tumor suppressor FAM134B (family with sequence similarity 134, member B) in colon cancer, examine the potential gene regulators of FAM134B expression and its impact on mitochondrial function. FAM134B was overexpressed in colon cancer and non-neoplastic colonic epithelial cells. Various cell-based assays including apoptosis, cell cycle, cell proliferation, clonogenic, extracellular flux and wound healing assays were performed. Western blot analysis was used to confirm and identify potential interacting partners of FAM134B in vitro . Immunohistochemistry and qPCR were employed to determine the expressions of MIF and FAM134B, respectively, on 63 patients with colorectal carcinoma. Results showed that FAM134B is involved in the cell cycle and mitochondrial function of colon cancer. Overexpression of FAM134B was coupled with increased expression levels of APC, p53, and MIF. Increased expression of both APC and p53 further validates the potential role of tumor suppressor FAM134B in regulating cancer progression through the WNT/ß-catenin signaling pathway. In approximately 70% of the patients with colorectal cancer, FAM134B downregulation was correlated with MIF protein overexpression while the remaining 30% showed concurrent expression of FAM134B and MIF ( P = .045). High expression of MIF coupled with low expression of FAM134B is associated with microsatellite instability status in colorectal carcinomas ( P = .049). FAM134B may exert its tumor suppressive function through affecting cell cycle, mitochondrial function via potentially interacting with MIF and p53.